IMPLEMENTASI MANAJEMEN RANTAI PASOK DAN KETERLIBATAN STAKEHOLDER PADA INDUSTRI KAROSERI MOBIL - A Rony Yulianto; Dewi Apriani Fr (Multiplier: Jurnal Magister Manajemen, 2018)
The purpose of this study is to find out the supply chain map of raw materials from carrosseries industry suppliers; analyze supply chain management in the car body industry; and knowing the involvement of stakeholders in influencing the development of the bodybuilding industry. This research was conducted with literature studies based on literature sources in the form of articles and reports from previous research results. The supply chain that is applied is the flow of raw material from the supplier, goes to the purchasing department, then goes to the warehouse and production section. Supply chain management applied by the company is guided by the Standard Operating Procedure (SOP) in each part to maintain product quality. The development of car body industry companies depends on the involvement of stakeholders: government, suppliers, employees, distributors and consumers.Keywords: supply chain management, stakeholders, car body industry